The effects of reprocessing and fiber treatments on the properties of polypropylene-sugarcane bagasse biocomposites (2020)
This study explores the reprocessing behavior of polypropylene-sugarcane bagasse biocomposites using neat and chemically treated bagasse fibers (20 wt.%). iocomposites were reprocessed 5 times using the extrusion process followed by injection molding. The mechanical properties indicate that microfibers bagasse fibers addition and chemical treatments generate improvements in the mechanical properties, reaching the highest performance in the third cycle where the flexural modulus and flexural strength increase 57 and 12% in comparison with neat PP. differential scanning calorimetry (DSC) and TGA characterization show that bagasse fibers addition increases the crystallization temperature and thermal stability of the biocomposites 7 and 39 °C respectively, without disturbing the melting process of the PP phase for all extrusion cycles. The rheological test shows that viscosity values of PP and biocomposites decrease progressively with extrusion cycles; however, Cole–Cole plots, dynamic mechanical analysis (DMA), width at half maximum of tan delta peaks and SEM micrographs show that chemical treatments and reprocessing could improve fiber dispersion and fiber–matrix interaction. Based on these results, it can be concluded that recycling potential of polypropylene-sugarcane bagasse biocomposites is huge due to their mechanical, thermal and rheological performance resulting in advantages in terms of sustainability and life cycle impact of these materials